PENGARUH STRUKTUR KEPEMILIKAN, AUDITOR EKSTERNAL DAN KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Elva Ikhwani Andiana, (2022)
This study was conducted to determine the significant effect of ownership structure (institutional ownership, managerial ownership, ownership concentration), external auditors and environmental performance on the disclosure of Corporate Social Responsibility (CSR). CSR disclosure is measured using topicspecific indicators of the Global Reporting Initiative (GRI) Standards which consist of economic, environmental and social disclosures with a total of 89 disclosure items. The object of this research is non-financial companies listed on the Indonesia Stock Exchange in 2018 - 2020. The sampling technique used is purposive sampling with a total of 77 samples. This study uses STATA data processing software version 16. The results of this study indicate that institutional ownership, ownership concentration, external auditors and environmental performance partially have no significant effect on CSR disclosure. Meanwhile, managerial ownership has a significant negative effect on CSR disclosure.